Symptoms and clinic of postmenopausal vulvovaginal atrophy in different stages of postmenopause: A cross sectional study - Liana Z. Ziganshina; Sofia Yu. Muslimova; Indira V. Sakhautdinova; Elmira M. Zulkarneeva (IP Berlin A.V., 2023)
Hypoestrogenism associated with menopause has a strong negative effect on the condition of the vagina and urinary tract, and often leads to the development of genitourinary menopausal syndrome, significantly disrupting the quality of life of women. Menopausal vulvovaginal atrophy is diagnosed in 36 to 90% of peri- and postmenopausal women. In recent years, it has been revealed that this condition is also present in 19% of women aged 4045 years during premenopause. Aim. The aim of the study was to study the relationship between the dynamics of the severity of symptoms and their impact on the quality of life of women, and the clinical manifestations of postmenopausal atrophic vaginitis, depending on the stage of postmenopause. Results. Patients in the early postmenopausal period had a vaginal health index consistent with moderate atrophy. Throughout the postmenopausal period studied, clinical manifestations of vaginal atrophy progressed, and in the late menopausal period, the vaginal health index was consistent with severe atrophy. Conclusion. In our opinion the therapy of vulvovaginal atrophy should begin with the period of early menopause. At this time, women are most interested in treatment, as their quality of life suffers significantly due to the newly appeared extremely unpleasant sensations. At the same time, minor atrophic changes in the tissues of the vagina and vulva are easier to treat.